2020
DOI: 10.1136/svn-2019-000305
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral small vessel disease or intracranial large vessel atherosclerosis may carry different risk for future strokes

Abstract: BackgroundThe effect of cerebral small vessel disease (CSVD) and intracranial arterial stenosis (ICAS) on stroke outcomes remains unclear.MethodsData of 1045 patients with minor stroke or transient ischaemic attack (TIA) were obtained from 45 sites of the Clopidogrel in High-Risk Patients with Acute Non-disabling Cerebrovascular Events (CHANCE) trial. We assessed the associations of burdens of CSVD and ICA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The findings of this study are consistent with those of other recently reported trials ( 13 , 15 ), which indicated that the presence of WMH on baseline magnetic resonance imaging is not independently associated with an increased risk of stroke recurrence in patients with ICAS. The coexistence of intracranial atherosclerosis with changes in white matter may predict an unfavorable functional outcome at 1 year.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of this study are consistent with those of other recently reported trials ( 13 , 15 ), which indicated that the presence of WMH on baseline magnetic resonance imaging is not independently associated with an increased risk of stroke recurrence in patients with ICAS. The coexistence of intracranial atherosclerosis with changes in white matter may predict an unfavorable functional outcome at 1 year.…”
Section: Discussionsupporting
confidence: 93%
“…A study from the SAMMPRIS trial showed that the presence of SVD on baseline magnetic resonance imaging was not independently associated with an increased risk of stroke in patients with ICAS ( 13 ). Data from the CHANCE trial found that SVD was associated with more disability and bleeding events and that ICAS is associated with an increased risk of stroke and disability in patients with minor stroke and TIA at 3 months, which implies that SVD and ICAS may represent different vascular pathologies and play distinct roles in stroke outcomes ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of ICAD has been associated with an increased risk of recurrent stroke and disability following minor stroke and TIA [7][8][9]. Antiplatelet therapy, risk factor modification and lifestyle changes are the current standard of care for symptomatic ICAD [10].…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial arterial stenosis was demonstrated to be associated with an increased risk of stroke and disability in minor stroke [ 10 ]. The infarct progression in patients with severe stenosis/occlusion of large vessels is one of the main causes of neurological deterioration in AIS patients [ 11 ], while a considerable number of these patients initially present mild symptoms.…”
Section: Introductionmentioning
confidence: 99%